MANAGING INNOVATION IN INDUSTRIAL POLICY: INTERNATIONAL EXPERIANCE AND ITS ADAPTABILITY IN THE RUSSIAN CONDITIONS - J. Proskurina (Вестник университета, 2016)
The article discusses the features of industrial policy in foreign countries engaged in various types of industrial policy; the possibility of using foreign experience in Russia.